2007
DOI: 10.1136/bmj.39225.458218.94
|View full text |Cite
|
Sign up to set email alerts
|

Routine testing to reduce late HIV diagnosis in France

Abstract: Although around half the French population has had an HIV test, many people are still not diagnosed until the disease is advanced. Cyrille Delpierre and colleagues believe the answer is to expand routine testing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 16 publications
1
22
1
Order By: Relevance
“…The same may hold for other countries in Europe and North America, where the median CD4 at start of ART is low [28]. In view of the marked differences in mortality when comparing late-presenting individuals to those presenting earlier, our results argue in favour of expanded HIV testing [29][30][31]. These arguments are complemented by our results, which demonstrate that in individuals with timely HIV diagnosis ART is initiated promptly before a further drop of CD4 T-cells.…”
Section: Discussionsupporting
confidence: 74%
“…The same may hold for other countries in Europe and North America, where the median CD4 at start of ART is low [28]. In view of the marked differences in mortality when comparing late-presenting individuals to those presenting earlier, our results argue in favour of expanded HIV testing [29][30][31]. These arguments are complemented by our results, which demonstrate that in individuals with timely HIV diagnosis ART is initiated promptly before a further drop of CD4 T-cells.…”
Section: Discussionsupporting
confidence: 74%
“…Another French study found that being in a steady relationship and having children make people feel that they are less at risk for HIV and cause them to be at greater risk for late diagnosis (Delpierre et al, 2006). Generally speaking, since they are not priority targets for testing, current French policy results in people at low risk for HIV infection being at high risk for late detection (Delpierre, Cuzin, & Lert, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Broadly, rates of late diagnosis have either remained the same or increased [6]. Confronted with substantial numbers of individuals who are unaware of their HIV status, there have been calls in a number of countries in Europe for an increase in HIV testing as well as an extension of provider-initiated routine opt-out testing [7,8].…”
Section: Discussionmentioning
confidence: 99%